The expression of OsPLA2-III and OsPPO genes in rice (Oryza sativa L.) under Fe toxicity stress - Turhadi, .; Hamim, .; Ghulamahdi, Munif; Miftahudin, . (Journal of Tropical Life Science, 2021)
Lipid is an important biomolecule in plant because of their structural and functional roles in plant cells. Moreover, lipid could be a signal molecule in defense system of plants under biotic and abiotic stresses. Detoxification process of toxic substances, which is one of the defense system and controlled by various genes, plays an important role in tolerance mechanism in plant under stress conditions, including iron (Fe) toxicity. Plants develop various tolerance strategies to cope the Fe toxicity. The objective of this research was to investigate the expression of OsPLA2-III and OsPPO genes under Fe stress condition. Two-weeks-old seedlings of two rice varieties, i.e., IR64 (Fe-sensitive toxicity) and Pokkali (Fe-tolerant toxicity) were used. Both varieties were treated with 1 (control) and 400 ppm of Fe in the form of FeSO4.7H2O in the nutrient culture solution. The leaf bronzing, chlorophyll content, and relative expression of OsPLA2-III and OsPPO genes were observed. An in-silico study was also performed to predict the interaction between OsPLA2-III and OsPPO proteins. The results showed that the Fe toxicity induced leaf bronzing, reduced leaf chlorophyll content, and increased the OsPLA2-III and OsPPO gene expression levels. Both genes are suggested to have a role in plant tolerance mechanism during Fe toxicity stress via lipid signaling pathway.